Precoded random spreading multiple access system in AWGN channels. - Jang, W.M.
In this paper, we compare the asymptotic performance of the decorrelator approaches to multiuser detection in code-division multiple-access (CDMA). Precoding is the decorrelation which is performed at a common transmitter such as the base station or satellite that allows single-user detection at the handset receiver. Receiver-based decorrelator decorrelates multiple user signals at the receiver side. We analyze the performance of the aforementioned decorrelation approaches with time-varying random spreading sequences in additive white Gaussian noise channels. The results demonstrate that the performance of precoding and that of receiver-based decorrelator are asymptotically equivalent.
Keywords: AWGN channels; CDMA; Additive white Gaussian noise channels; Base station; Code division multiple access; Decorrelator approach; Handset receiver; Multiuser detection; Precoded random spreading multiple access system; Satellite; Single-user detection; Time-varying random spreading sequences; Transmitter